Abnormalities of pigmentation following UVB exposure and incorrect applicatio of calcipotriol ointment and tazarotene gel for psoriasis - Stinco, G... (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 1999)
We present two cases where an incorrect application of the topical therapy in association with UVB phototherapy caused hyper- or hypopigmented skin lesions.CASE 1. A 48-year-old man with plaque psoriasis treated with calcipotriol ointment plus UVB phototherapy. Although correctly instructed, onone occasion he applied the calcipotriol ointment a few minutes before the UVB exposure. Some hours later he presented numerous irregular hypopigmented areas around the psoriatic lesions. The calcipotriol therapy plus UVB phototherapy was continued and the hypopigmentation areas gradually cleared inabout a month. CASE 2. A 48-year-old man with plaque psoriasis treated with tazarotene 0.1 % gel plus UVB phototherapy Although correctly instructed, he applied tazarotene gel one hour before the UVB exposure. The results was the sudden appearance of numerous dark-brown hyperpigmentation in the form of asymptomatic round or oval patches on the site of psoriatic lesions involving his trunk and limbs. The treatment was discontinued and the hyperpigmentated patches lasted for a further 6 months.
Keywords: Adverse effects; Cholecalciferol; Drug therapy; Hyperpigmentation; Ointments; Psoriasis; Retinoids; Therapy; Treatment outcome; Ultraviolet therapy